PANIC ATTACK AKIBAT COVID-19 (Sebuah Studi pada Mahasiswa UIN Sunan Kalijaga Yogyakarta) - Citra Widyastuti; Raidatul Saptrians; Nurul Miftahatul Ulumiyah (UIN Sunan Kalijaga Yogyakarta, 2021)
Pandemic situation it triggered panic attacks, one of which is against students. Panic attacks can be caused by several things, such as social distancing which causes people to feel lonely, bored, and isolated. A pandemic situation like this has quite an impact on human psychology. Feelings of anxiety, fear, and anxiety result in panic attacks that have quite an impact on him and others. A person who experiences a panic attack can be seen from two aspects, namely physical and psychological aspects. Panic attacks can be caused by biological, psychological, and environmental factors. The purpose of this study was to determine panic attacks against students of UIN Sunan Kalijaga Yogyakarta. The subjects of this study were 100 respondents who came from students of UIN Sunan Kalijaga Yogyakarta. This study uses a type of quantitative descriptive research method. The results of this study were UIN Sunan Kalijaga students experienced panic attacks. A total of 100 respondents obtained 8% experienced panic attacks in the low category, 84% in the moderate category and 8% in the high category from students of UIN Sunan Kalijaga Yogyakarta with symptoms such as restlessness, anxiety, excessive worry, sweating and withdrawing.Keywords: panic attack, covid 19, UIN students